1992
DOI: 10.7326/0003-4819-116-3-183
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) as an Adjunct to Autologous Hemopoietic Stem Cell Transplantation for Lymphoma

Abstract: Administration of GM-CSF after autologous hemopoietic stem cell transplantation in patients with lymphoma resulted in accelerated myeloid recovery, particularly in patients who received peripheral blood stem cells and nonpurged bone marrow, and was associated with a decreased incidence of bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…[11][12][13][14] However, as happens in different settings, the fact that the neutrophil recovery is shortened after administration of conventional doses of chemotherapy does not necessarily translate into a clinical benefit. 25 Some of the randomized studies performed to address the issue of the role of hematopoietic growth factors (G and GM-CSF) in the transplantation setting have shown that the faster time to neutrophil recovery correlates with a shorter hospitalization time, [11][12][13]24,[26][27][28] and fewer infectious complications or less antibiotic use. 24,26,28 However, others have demonstrated only a modest clinical benefit 14 and yet other studies have found no clinical benefit of administering growth factors following transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] However, as happens in different settings, the fact that the neutrophil recovery is shortened after administration of conventional doses of chemotherapy does not necessarily translate into a clinical benefit. 25 Some of the randomized studies performed to address the issue of the role of hematopoietic growth factors (G and GM-CSF) in the transplantation setting have shown that the faster time to neutrophil recovery correlates with a shorter hospitalization time, [11][12][13]24,[26][27][28] and fewer infectious complications or less antibiotic use. 24,26,28 However, others have demonstrated only a modest clinical benefit 14 and yet other studies have found no clinical benefit of administering growth factors following transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already demonstrated the feasibility of PBPC (Brugger el al., 1992;Siena el al., 1989;Kessinger el al., 1989;Advani el al., 1992;Richel, 1992;Richel el al., 1993). Our results confirm that PBPC is an effective alternative to ABMT.…”
Section: Discussionmentioning
confidence: 99%
“…It is introduced as an alternative to autologous bone marrow transplantation (ABMT) and has several advantages over ABMT, such as avoiding anaesthesia. It seems that infusion of PBPC after high-dose chemotherapy is associated with markedly accelerated platelet and neutrophil recovery as compared to ABMT (Kessinger et al, 1989;Advani et al, 1992;Siena et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well known that prophylactic use of HGFs after myelosuppressive chemotherapy leads to a reduction in the incidence of febrile episodes3 the use of antibiotics and the number of days of hospitalisation for fever and/or infection [2][3][4]. EPO exerts its maximal activity at the level of the more differentiated erythroid precursor cells.…”
Section: Introductionmentioning
confidence: 99%